2018
DOI: 10.1016/j.idairyj.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structure of insoluble particles in reconstituted model infant formula powders

Abstract: a b s t r a c tPhase separation of insoluble particles, so called "white flecks", is a physical defect in reconstituted milk obtained from spray-dried, fat-containing dairy powders. Compared with bulk powder particles, white flecks have quite different chemical and morphological characteristics. They consist mainly of proteins and fat, forming a dense network. Here, two concurrent formation mechanisms are suggested based on the structures revealed by confocal microscopy imaging. Fused spherical particles with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Solubility time ranged from 40 to 58 s. The shortest time required in which microencapsulated milk powder was dissolved completely was achieved for sample A (40 s) and the longest time required for sample C (58 s). However, solubility of milk powder depends on the several factors such as atomization speed, heat treatment of milk, type of spray drying, and type of coating materials used ( Sharma et al., 2012 , Toikkanen et al., 2018 , Lee et al., 2018 ). It is reported that maltodextrin showed significantly shorter time period than dextrin.…”
Section: Resultsmentioning
confidence: 99%
“…Solubility time ranged from 40 to 58 s. The shortest time required in which microencapsulated milk powder was dissolved completely was achieved for sample A (40 s) and the longest time required for sample C (58 s). However, solubility of milk powder depends on the several factors such as atomization speed, heat treatment of milk, type of spray drying, and type of coating materials used ( Sharma et al., 2012 , Toikkanen et al., 2018 , Lee et al., 2018 ). It is reported that maltodextrin showed significantly shorter time period than dextrin.…”
Section: Resultsmentioning
confidence: 99%
“…For each sample, there will be a different set of quality characteristics, because of the varied surface tension of components, such as protein, fats, carbohydrates, vitamin, and minerals in the powder when it comes in contact with water (Fang, Selomulya, & Chen, 2007). The composition of insoluble particles primarily consists of fats and proteins that form a network when mixed with water (Toikkanen, Outinen, Malafronte, & Rojas, 2018). In a processing condition, the most important parameter that determines the physicochemical properties of powder while spray-drying is the inlet temperature which affects the moisture content and hygroscopicity of the powder (Santhalakshmy, Don Bosco, Francis, & Sabeena, 2015).…”
Section: Reconstitution Propertiesmentioning
confidence: 99%
“…The rate at which rehydrated IF powders destabilise, or "cream", is related to the extent of emulsification of fat by protein prior to spray-drying [2]. Similarly, the discrete visible and insoluble particles, known as white flecks, which are occasionally present post-rehydration of IF powders, have been shown by Toikkanen et al [21] to be linked to emulsion quality. Hydrolysis of whey proteins in IF can also be expected to affect emulsification and related properties such as creaming.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increase in the publications dealing with IF manufacture [2,6,7,21,[25][26][27][28]. Some publications [25,27,28] provided limited information regarding the physical properties of commercial IF and FO samples; however, it is difficult to discern usable information regarding the range of structures and physical properties present in commercial products from these studies.…”
Section: Introductionmentioning
confidence: 99%